Treating time effectively the first session in brief therapy - Budman, Simon H.; Kevin Dawkins Productions (New York : Guilford Press, 1994)
(Producer) Teaches viewers how to think about time and scheduling in a new way, focus on primary themes and issues, evaluate the patient's readiness for change, identify and reinforce the patient strengths, summarize and conclude a first session
Keywords: Psychotherapy, Brief -- methods